"The Tyranny of Merit: What’s Become of the Common Good. Farrar, Straus and Giroux" de Michael Sandel - Morales Bravo, Oscar Francisco (Revista Ethika+, 2021)
Reseña de Sandel, M. (2020). The Tyranny of Merit: What’s Become of the Common Good. Farrar, Straus and Giroux